2003
DOI: 10.1177/000992280304200107
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Dysfunction in Pediatric Patients

Abstract: The goals of this study were to describe the pattern of voiding disorders in children in our community, to describe clinical criteria for making the specific diagnoses, and to comment on management. The medical records of 226 children referred because of voiding dysfunction or urinary tract infections (UTI) were evaluated. Children with normal voiding patterns when uninfected, with monosymptomatic nocturnal enuresis, and with known neurologic or anatomic abnormalities were excluded. Detrusor instability, an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 22 publications
0
46
0
8
Order By: Relevance
“…When urinary urgency is not followed by holding maneuvers, there is no risk of UTI, but there is a possibility of diurnal urinary incontinence. 13 Voiding dysfunction is a wide term that indicates an abnormal urinary pattern for the age of the child, 14 which is not usually recognized before daytime bladder control, has been achieved. 7 The literature shows an increase in prevalence rates for voiding dysfunction over recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When urinary urgency is not followed by holding maneuvers, there is no risk of UTI, but there is a possibility of diurnal urinary incontinence. 13 Voiding dysfunction is a wide term that indicates an abnormal urinary pattern for the age of the child, 14 which is not usually recognized before daytime bladder control, has been achieved. 7 The literature shows an increase in prevalence rates for voiding dysfunction over recent years.…”
Section: Discussionmentioning
confidence: 99%
“…7 The literature shows an increase in prevalence rates for voiding dysfunction over recent years. [14][15][16] However, Bakker 16 questions whether this increase is real, or whether it could be the result of parents increased knowledge of the existence of treatment for the problem. In the present study it was observed that the great majority of parents did not recognize the symptoms and explained holding maneuvers and urgency as laziness or leaving it till the last minute because playing.…”
Section: Discussionmentioning
confidence: 99%
“…The term cannot be applied unless repeated uro£ow measurements have shown curves with a staccato patternöor if veri¢ed by invasive urodynamic investigation. Note that the term describes malfunction during the voiding phase only, it says nothing about the storage phase.The usage of this expression to denote any kind of disturbed LUT function [Hellerstein and Linebarger, 2003], leads to confusion and is strongly discouraged. Dysfunctional voiding means dysfunction during voiding.…”
Section: Day-time Conditionsmentioning
confidence: 99%
“…This condition, as a common problem in children, makes up more than 40% of pediatric urology clinic visits (4,5). Children with Pollakiuria show extraordinary daytime urinary frequency, urination every 15 to 20 minutes per day without nocturnal enuresis, urinary incontinence, dysuria, and urinary tract infections (UTIs) (6).…”
Section: Introductionmentioning
confidence: 99%